Gab2 and Gab3 Redundantly Suppress Colitis by Modulating Macrophage and CD8+ T-Cell Activation - Wang, Zhengqi; Vaughan, Tamisha Y.; Zhu, Wandi; Chen, Yuhong; Fu, Guoping; Medrzycki, Magdalena; Nishio, Hikaru; Bunting, Silvia T.; Hankey-Giblin, Pamela A.; Nusrat, Asma; Parkos, Charles A.; Wang, Demin; et al. (Frontiers in Immunology, 2019)
Inflammatory Bowel Disease (IBD) is a multi-factorial chronic inflammation of the gastrointestinal tract prognostically linked to CD8+ T-cells, but little is known about their mechanism of activation during initiation of colitis. Here, Grb2-associated binding 2/3 adaptor protein double knockout mice (Gab2/3−/−) were generated. Gab2/3−/− mice, but not single knockout mice, developed spontaneous colitis. To analyze the cellular mechanism, reciprocal bone marrow (BM) transplantation demonstrated a Gab2/3−/− hematopoietic disease-initiating process. Adoptive transfer showed individual roles for macrophages and T-cells in promoting colitis development in vivo. In spontaneous disease, intestinal intraepithelial CD8+ but much fewer CD4+, T-cells from Gab2/3−/− mice with rectal prolapse were more proliferative. To analyze the molecular mechanism, reduced PI3-kinase/Akt/mTORC1 was observed in macrophages and T-cells, with interleukin (IL)-2 stimulated T-cells showing increased pSTAT5. These results illustrate the importance of Gab2/3 collectively in signaling responses required to control macrophage and CD8+ T-cell activation and suppress chronic colitis.